2015
DOI: 10.11144/javeriana.upsy14-2.abss
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre calidad del servicio deportivo, valor y satisfacción de usuarios en España

Abstract: r e s u m e N Los modelos conceptuales facilitan la gestión de los servicios deportivos que explican, pero los desarrollados en otros países no ofrecen garantías para ser reproducidos correctamente en España. El objetivo del estudio fue comprobar la reproducibilidad del modelo de evaluación de los servicios deportivos propuesto por Murray y Howat (2002), en el contexto de las organizaciones deportivas en España. En una muestra de 2667 usuarios de servicios deportivos españoles, se relacionaron los conceptos ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
2
10
4
4
Order By: Relevance
“…These results coincide with the results obtained in other publications [31,35,[62][63][64]. However, Nuviala et al [47] found no statistical relationship between value and satisfaction using structural equations, and attributed this to the affective nature of satisfaction [64]. The differences between these two studies may be due to contextual differences, since according to Ledden, Kalafatis, and Mathioudakis [65], these play an important role in how functional relationships behave.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results coincide with the results obtained in other publications [31,35,[62][63][64]. However, Nuviala et al [47] found no statistical relationship between value and satisfaction using structural equations, and attributed this to the affective nature of satisfaction [64]. The differences between these two studies may be due to contextual differences, since according to Ledden, Kalafatis, and Mathioudakis [65], these play an important role in how functional relationships behave.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, lower satisfaction with a service is associated with lower customer loyalty [46]. In the field of sports services, studies by Nuviala et al [47] and Theodorakis et al [31] also show this positive influence of satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the managers are aware that quality is a sine qua non of satisfaction with the service (Alén & Fraiz, 2006) and that managing this quality is the greatest potential growth of their companies (Lloréns & Fuentes, 2000). Along these lines, Nuviala, Grao-Cruces, Fernández-Ozcorta and Nuviala (2015) conclude that quality is a necessary condition of users' perceived value and satisfaction with the sports service. Therefore, the managers in the study may have recognised it as more important to respond to these quality processes, given that satisfactorily managing them may give them an edge over the competition by improving the perception of their sports service in clients' eyes.…”
Section: Discussionmentioning
confidence: 98%
“…Possiblement els gestors saben que la qualitat és un antecedent en la satisfacció amb el servei (Alén & Fraiz, 2006) i que la seva gestió és el major potencial de creixement de les empreses (Lloréns & Fuentes, 2000). En aquesta línia, Nuviala, Grau-Creuis, Fernández-Ozcorta i Nuviala (2015) conclouen que la qualitat és un antecedent del valor percebut i de la satisfacció dels usuaris amb el servei esportiu. Per tant, els gerents de l'estudi podrien haver reconegut com més important donar resposta a aquests processos de qualitat, ja que la seva gestió satisfactòria podria donar-los un avantatge competitiu enfront de la competència, millorant la percepció del seu servei esportiu enfront del client.…”
Section: Discussionunclassified
“…www.efsupit.ro 1317 subjective and different to objective or real quality (Zeithaml, 1988). Various studies support the opinion that perceived quality is positively associated to perceived value, being this a precedent of it (Calabuig, Prado-Gascó, Crespo, Núñez-Pomar and Añó, 2015;Chen and Dubinsky, 2003;Nuviala, Grao-Cruces, Fernández-Ozcorta and Nuviala, 2015). In the same way, the reviewed literature shows that perceived value can be a good predictor of the satisfaction of the client.…”
Section: Introductionmentioning
confidence: 92%